A Bacterial Expression Vector Archive (BEVA) for Flexible Modular Assembly of Golden Gate-Compatible Vectors - Geddes, Barney A.; Mendoza-Suárez, Marcela A.; Poole, Philip S. (Frontiers in Microbiology, 2019)
We present a Bacterial Expression Vector Archive (BEVA) for the modular assembly of bacterial vectors compatible with both traditional and Golden Gate cloning, utilizing the Type IIS restriction enzyme Esp3I, and have demonstrated its use for Golden Gate cloning in Escherichia coli. Ideal for synthetic biology and other applications, this modular system allows a rapid, low-cost assembly of new vectors tailored to specific tasks. Using the principles outlined here, new modules (e.g., origin of replication for plasmids in other bacteria) can easily be designed for specific applications. It is hoped that this vector construction system will be expanded by the scientific community over time by creation of novel modules through an open source approach. To demonstrate the potential of the system, three example vectors were constructed and tested. The Golden Gate level 1 vector pOGG024 (pBBR1-based broad-host range and medium copy number) was used for gene expression in laboratory-cultured Rhizobium leguminosarum. The Golden Gate level 1 vector pOGG026 (RK2-based broad-host range, lower copy number and stable in the absence of antibiotic selection) was used to demonstrate bacterial gene expression in nitrogen-fixing nodules on pea plant roots formed by R. leguminosarum. Finally, the level 2 cloning vector pOGG216 (RK2-based broad-host range, medium copy number) was used to construct a dual reporter plasmid expressing green and red fluorescent proteins.